Comparative law
1 online resource (vi, 188 pages).
Keywords: "This book discusses a number of important themes in comparative law: legal metaphors and methodology, the movements of legal ideas and institutions and the mixity they produce, and marriage, an area of law in which culture - or clashes of legal and public cultures - may be particularly evident. In a mix of methodological and empirical investigations divided by these themes, the work offers expanded analyses and a unique cross-section of materials that is on the cutting edge of comparative law scholarship. It presents an innovative approach to legal pluralism, the study of mixed jurisdictions, and to language and the law, with the use of metaphors not as illustration but core element of comparative methodology"--